Persistent eNOS activation secondary to caveolin-1 deficiency induces pulmonary hypertension in mice and humans through PKG nitration - You-Yang Zhao; Yidan D. Zhao; Muhammad K. Mirza; Julia H. Huang; Hari-Hara S.K. Potula; Steven M. Vogel; Viktor Brovkovych; Jason X.-J. Yuan; John Wharton; Asrar B. Malik (The Journal of Clinical Investigation, 2009)
Pulmonary hypertension (PH) is an unremitting disease defined by a progressive increase in pulmonary vascular resistance leading to right-sided heart failure. Using mice with genetic deletions of caveolin 1 (Cav1) and eNOS (Nos3), we demonstrate here that chronic eNOS activation secondary to loss of caveolin-1 can lead to PH. Consistent with a role for eNOS in the pathogenesis of PH, the pulmonary vascular remodeling and PH phenotype of Cav1–/– mice were absent in Cav1–/–Nos3–/– mice. Further, treatment of Cav1–/– mice with either MnTMPyP (a superoxide scavenger) or l-NAME (a NOS inhibitor) reversed their pulmonary vascular pathology and PH phenotype. Activation of eNOS in Cav1–/– lungs led to the impairment of PKG activity through tyrosine nitration. Moreover, the PH phenotype in Cav1–/– lungs could be rescued by overexpression of PKG-1. The clinical relevance of the data was indicated by the observation that lung tissue from patients with idiopathic pulmonary arterial hypertension demonstrated increased eNOS activation and PKG nitration and reduced caveolin-1 expression. Together, these data show that loss of caveolin-1 leads to hyperactive eNOS and subsequent tyrosine nitration–dependent impairment of PKG activity, which results in PH. Thus, targeting of PKG nitration represents a potential novel therapeutic strategy for the treatment of PH.